ESTUDIO EMPÍRICO DEL TRASTORNO NARCISISTA DE LA PERSONALIDAD (TNP) - Millán Vásquez de la Torre, Genoveva; Trechera, José Luis; Fernández Morales, Emilio (Acta Colombiana de Psicología, 2008)
This research aims at getting deep into the description and assessment of narcissistic personality disorder (NPD). Firstly, we de.ne NPD by four characteristics: false self-image, lack of empathy, sensitivity to criticism and disturbances in interpersonal relationships. Taking from a sample of 1025 persons, we elaborated a 15items test to measure NPD with three factors: narcissism, Machiavellianism and dominance. At the same time, we elaborated two tests, lack of empathy and exhibitionism, related to narcissistic pathology. The results con.rm the multifactor structure of the concept (NPD), .nding important differences between NPD in the Spanish and the American contexts as well as signi.cant relations with the Mehrabian and Epstein Tests, the Ma4 Scale by Harris and Lingoes and the NPI by Raskin and Hall. In addition, there were signi.cant relations between NPD and different variables such as age and gender